Kinetics of CrPV and HCV IRES-mediated eukaryotic translation using single-molecule fluorescence microscopy - Bugaud, Olivier (RNA, 2017)
Protein synthesis is a complex multistep process involving many factors that need to interact in a coordinated manner to properly translate the messenger RNA. As translating ribosomes cannot be synchronized over many elongation cycles, single-molecule studies have been introduced to bring a deeper understanding of prokaryotic translation dynamics. Extending this approach to eukaryotic translation is very appealing, but initiation and specific labeling of the ribosomes are much more complicated. Here, we use a noncanonical translation initiation based on internal ribosome entry sites (IRES), and we monitor the passage of individual, unmodified mammalian ribosomes at specific fluorescent milestones along mRNA. We explore initiation by two types of IRES, the intergenic IRES of cricket paralysis virus (CrPV) and the hepatitis C (HCV) IRES, and show that they both strongly limit the rate of the first elongation steps compared to the following ones, suggesting that those first elongation cycles do not correspond to a canonical elongation. This new system opens the possibility of studying both IRES-mediated initiation and elongation kinetics of eukaryotic translation and will undoubtedly be a valuable tool to investigate the role of translation machinery modifications in human diseases.